Tidal energy machines: A comparative life cycle assessment study. (May 2015) - Walker, Stuart; Howell, Robert; Hodgson, Peter; Griffin, Allan
Marine energy in the United Kingdom is undergoing a period of growth in terms of development and implementation. The current installed tidal energy capacity is expected to rise to provide 20% of the United Kingdom's electricity demand by 2050. This article used life cycle assessment to study four tidal energy devices, comparing their embodied energy and carbon dioxide emissions. The device designs studied included a multi-blade turbine, two three-blade horizontal axis turbine machines and an Archimedes' screw device. These machines were chosen to represent a cross section of design for the device, foundation, installation and operation. Embodied energy was considered over the lifetime of each device. Energy use from fabrication, transport, installation, maintenance, decommissioning and recycling was all calculated and compared to the energy generated by each device. Finally, the embodied energy, CO2 intensity and energy payback periods were compared to those of conventional power generating systems and other renewable energy sources. Devices were studied based on a functional unit, defined as a 10 MW array installed for 100 years. Of the devices studied, the OpenHydro Open Centre turbine was found to have the best ratio of generated to embodied energy. All devices achieved CO2 and energy payback within 12 years and exhibited CO2 intensity between 18 and 35 gCO2 /kW h. This compares favourably against current energy sources such as wind (8–12 gCO2 /kW h), solar photovoltaic (~30 gCO2 /kW h), nuclear (~70 gCO2 /kW h) and coal (~1000 gCO2 /kW h).